Liver Venous Deprivation or Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy?: A Retrospective Multicentric Study. Issue 5 (29th November 2021) - Chebaro, Alexandre; Buc, Emmanuel; Durin, Thibault; Chiche, Laurence; Brustia, Raffaele; Didier, Alexandre; Pruvot, François-René; Kitano, Yuki; Muscari, Fabrice; Lecolle, Katia; Sulpice, Laurent; Sonmez, Ercin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To compare 2 techniques of remnant liver hypertrophy in candidates for extended hepatectomy: radiological simultaneous portal vein embolization and hepatic vein embolization (HVE); namely LVD, and ALPPS. Background: Recent advances in chemotherapy and surgical techniques have widened indications for extended hepatectomy, before which remnant liver augmentation is mandatory. ALPPS and LVD typically show higher hypertrophy rates than portal vein embolization, but their respective places in patient management remain unclear. Methods: All consecutive ALPPS and LVD procedures performed in 8 French centers between 2011 and 2020 were included. The main endpoint was the successful resection rate (resection rate without 90-day mortality) analyzed according to an intention-to-treat principle. Secondary endpoints were hypertrophy rates, intra and postoperative outcomes. Results: Among 209 patients, 124 had LVD 37 [13, 1015] days before surgery, whereas 85 underwent ALPPS with an inter-stages period of 10 [6, 69] days. ALPPS was mostly-performed for colorectal liver metastases (CRLM), LVD for CRLM and perihilar cholangiocarcinoma. Hypertrophy was faster for ALPPS. Successful resection rates were 72.6% for LVD ± rescue ALPPS (n = 6) versus 90.6% for ALPPS ( P < 0.001). Operative duration, blood losses and length-of-stay were lower for LVD, whereas 90-day major complications and mortality were comparable. Results were globally unchanged for CRLM patients, or after excluding the early 2 years of experience (learning-curve effect). Conclusions: This study is the first 1 comparing LVD versus ALPPS in the largest cohort so far. Despite its retrospective design, it yields original results that may serve as the basis for a prospective study.